Realignment In the International System of Tariffs: The Effects of the Tariff War in the Making - Martin SCHMIDT-SCHWEFLINGHAUS (Communications of International Proceedings, 2025)
The tariffs that US President Trump has put on many countries are disrupting in many regards. He apparently follows a guide that was outlined by economist Stephen Miran in November 2024. One of the main questions that comes to mind is whether an escalating situation could cause severe harm to an over-leveraged world economy in which practically all major countries are already suffering from a burden of massive debts. A severe recession could turn the major debtor nations into failing entities. Historical precedence may or may not be the right point of reference. For the better part of its existence, the budget of US federal government almost totally relied upon revenues from tariffs. Apart from the fact that this system created by the first secretary of the treasury under President George Washington Alexander Hamilton (1789-1795) had many opponents at that time with legal and economic objections being brought up (Alexander Hamilton wanted to protect the US´s ´infant industries` after independence), it has to be mentioned that the US government was infinitely smaller than it is today, so that the revenue generated by these tariffs could be sustained. Moreover, the US Dollar has been the reserve currency of the world since the Bretton Woods conference of 1944, and China has turned into a major economic player after its admission to the World Trade Organization in 2001. In so far, the tariff environment of the 19th century must be considered an economic universe far away from the world in which we live. It was through the adoption of the 16th Amendment that the federal income tax as an alternative revenue system was introduced in 1913. Whether the tariffs are a negotiating tool to bring about other objectives or whether they are meant to stay permanently, remains to be seen.
Keywords: Introduced tariffs by the 2025 Trump administration; Former tariff structure within the U.S.; International trade order; US Dollar as the world´s reserve currency; Restructuring trade imbalances